FUNCTIONS OF EDUCATION SYSTEM MANAGEMENT AND ITS PROBLEMS IN THE MODERN ERA TODAY - Limsi; Siti Inganah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This paper examines the functions of education management and its challenges in the modern era. It highlights the critical role of education in shaping superior and adaptive human resources amidst technological advancements and globalization. The study discusses the main functions of education management, including planning, implementation, supervision, and evaluation, emphasizing the importance of aligning these functions with contemporary needs such as social competence and creativity. It also addresses challenges such as digital disparities, teacher quality, and curriculum adaptation, advocating for strategic steps to ensure national education can compete globally and benefit Indonesian society.